Skill-Related Adaptive Modifications of Gaze Stabilization in Elite and Non-Elite Athletes - van der Veen, Susanne M.; Stamenkovic, Alexander; Thomas, James S.; Pidcoe, Peter E. (Frontiers in Sports and Active Living, 2022)
The vestibular-ocular-reflex (VOR) provides gaze stability during head movements by driving eye movements in a direction opposite the head motion. Although vestibular-based rehabilitation strategies are available it is still unclear whether VOR can be modulated by training. By examining adaptations in gaze stabilization mechanisms in a population with distinct visuomotor requirements for task success (i.e., gymnasts), this study was designed to determine if experience level (as a proxy of training potential) was associated with gaze stabilization modifications during fixed target (VOR promoting) and slaved-to-head-movement targets (VOR suppressing) tasks. Thirteen gymnasts of different skill levels participated in a VOR and VOR suppression tasks. The gain between head and eye moments were calculated and compared between skill levels using an analysis of covariance. Across experience levels, there was a similar degradation in VOR gain away from -1 at higher movement speeds. However, during the suppression tasks, more experienced participants were able to maintain VOR gain closer to 0 across movement speeds, while novice participants showed greater variability in task execution regardless of movement speed. Changes in adaptive modifications to gaze stability associated with experience level suggest that the mechanisms impacting gaze stabilization can be manipulated through training.